Assessing the Health of Streams in Agricultural Landscapes: The Impacts of Land Management Change on Water Quality - Cruse, Rick; Huggins, Don; Lenhart, Christian; Magner, Joe; Royer, Todd; Schilling, Keith (Council for Agricultural Science and Technology (CAST), 2012)
The Clean Water Act of 1987 states that the elimination of pollutant discharge into navigable water is a national goal. Agriculture has been identified repeatedly as a significant contributor of nonpoint source pollution to surface waters. Despite conservation efforts, water quality problems still exist; all agricultural states struggle with balancing productive landscapes and water quality. Legislation, potential regulations, or allocations of millions of dollars to change agricultural practices seem warranted only if we know stream water is favorably impacted by modified agricultural practices, and in which streams the greatest potential impact might be observed.
Keywords: Land Management; Water Quality; Clean Water Act